HIPAA-COMPLIANT DATA INTEGRATION: BEST PRACTICES FOR MODERN HEALTHCARE SYSTEMS - Avinash Mavireddi (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Healthcare organizations face increasingly complex challenges in integrating and managing patient data while maintaining stringent security and compliance standards. This comprehensive technical article presents a structured framework for implementing secure, compliant, and scalable data integration solutions in healthcare environments. The article addresses critical aspects of modern healthcare data management, including HIPAA and GDPR compliance protocols, advanced encryption methodologies, role-based access control systems, and robust data governance frameworks. By examining real-world implementation strategies and emerging technologies, the actionable insights for healthcare IT professionals to develop resilient data integration architectures that protect patient information while enabling organizational growth. The framework presented incorporates industry best practices for cybersecurity, emphasizing threat prevention, incident response, and employee training while considering the scalability requirements of evolving healthcare systems.